PENGELOLAAN LIMBAH TERNAK UNTUK PRODUKSI TANAMAN DI DESA TLOGOPAKIS KECAMATAN PETUNGKRIYONO KABUPATEN PEKALONGAN - Sajuri Sajuri; Ubad Badrudin; Abdul Rosid; Fakhur Rozi; Dani Sulistyo Nugroho; Basa Aria Rizky Yonansha (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
Tlogopakis Village is one of the villages in the Petungkriyono sub-district, Pekalongan district, which is located in the highlands where the majority of the population works as farmers. Plants that are cultivated are mostly food and horticultural crops with the inputs applied so far still using inorganic fertilizers. Even though in this village there are many cows that produce waste. Meanwhile, the livestock waste has not been processed and managed properly, so it often causes problems to the environment in the form of environmental pollution. Seeing this condition, it is deemed necessary and urgent to do community service in the form of counseling with livestock waste management material for plant production. The activity was carried out on Friday, December 31, 2021 at the Rowo farmer group, Tlogopakis Village, Petungkriyono sub-district, Pekalongan district. The method is lecture, question and answer, and discussion. The results of community service activities showed that the participants who attended and participated in the activity were 17 farmers accompanied by 8 students, farmers were enthusiastic and enthusiastic in participating and attending these activities. This is shown by the patience of the farmers in participating in all events from start to finish without anyone leaving the place where the activities are taking place. Furthermore, when the discussion session was opened, many farmers responded by asking questions and providing suggestions and hoped that this activity could be carried out sustainably.Keywords: extension, farmers, livestock, waste